IMPLIKASI PENJERNIHAN PAHAM TENTANG ALLAH TERHADAP PASTORAL PENDAMPINGAN PENYINTAS HIV DAN AIDS - George Kirchberger (Jurnal Ledalero, 2015)
The author starts from the fact that often enough those who test positive for HIV, or who are suffering from AIDS, feel cursed by God, and question why God has punished them. They experience discrimination and are stigmatized by family and neighbours as sinners and punished by God. The author notes a similar way of thinking in the Bible. He then points to a corrective to this attitude and way of thinking as given in the Book of Job. He then takes up the thinking and actions of Jesus who approached people who were suffering discrimination and opposed the way of thinking that attributed suffering to a divine curse. Drawing from this biblicval corrective, the author outlines a number of conclusions for pastoral work in the Church at this time. Kata-kata kunci: HIV, AIDS, penyakit, kutuk, Ayub, Yesus, orang, sakit, pastoral, Gereja.